Effect of Eight Weeks Plyometric Training on Some Kinematic Parameters, Horizontal Jumping Power, Agility, and Body Composition in Elite Parkour Athletes - Abdolrasoul Daneshjoo; Soudabeh Raeisi (Islamic Azad University, Hamedan Branch, 2020)
Objective: A high correlation between lower limb explosive power and muscular strength, production of high power levels in the shortest time, and high level of agility are essential to achieve optimal performance in Parkour. It seems that polymetric exercises can make it possible to achieve the highest performance. In this regard, the aim of the present study was to investigate the effect of an 8-week plyometric exercise program on knee kinematic parameters, body composition, agility and horizontal jumping power of Parkour athletes. Methods: In this quasi-experimental study with pre-test and post-test design, 20 elite Parkour athletes aged 19-26 years were selected and randomly divided into two groups of exercise (n=10) and control (n=10). The exercise group carried out the program for eight weeks, three sessions per week, each for one hour. Before and after exercise, measurements of kinematic parameters of knee, agility, and horizontal jumping power, and body composition in subjects were performed. The collected data were analyzed using t-test considering a significant level of P≤0.05. Results: Plyometric exercise for eight weeks had a significant effect on knee kinematic parameters of Parkour athletes (P=0.003) and significantly improved their horizontal jump, agility and reduced body fat percentage (P≤0.05). Conclusion: Plyometric exercise can significantly improve kinematic parameters of the knee, increase the jumping power and agility, and reduce body fat percentage in Parkour athletes; however, since Parkour movements are very similar to plyometric exercises, more study is needed.